2002
DOI: 10.1021/es015710z
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic Springtime Depletion of Atmospheric Mercury

Abstract: Unlike other heavy metals that are inherently associated with atmospheric aerosols, mercury in ambient air exists predominantly in the gaseous elemental form. Because of its prolonged atmospheric residence time, elemental mercury vapor is distributed on a global scale. Recently, Canadian researchers have discovered that total gaseous mercury levels in the lower tropospheric boundary layer in the Canadian Arctic are often significantly depleted during the months after polar sunrise. A possible explanation may i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
234
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 299 publications
(264 citation statements)
references
References 21 publications
25
234
1
1
Order By: Relevance
“…The range of data is coherent with previous data measured in January 2009 at DC (Dommergue et al, 2012). The median concentration is significantly lower than measurements made on the Greenland ice cap (Faïn et al, 2008) but comparable to values retrieved both at coastal sites of Antarctica such as Neumayer Station (0.99±0.27 ng.m -3 (Ebinghaus et al, 2002, Temme et al, 2003, Terra Nova Bay (0.9±0.3 ng.m -3 (Sprovieri et al, 2002)), McMurdo (1.20±1.08 ng.m -3 (Brooks et al, 2008b) and the continental South Pole station 0.54 ± 0.19 ng.m -3 (Brooks et al, 2008a).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The range of data is coherent with previous data measured in January 2009 at DC (Dommergue et al, 2012). The median concentration is significantly lower than measurements made on the Greenland ice cap (Faïn et al, 2008) but comparable to values retrieved both at coastal sites of Antarctica such as Neumayer Station (0.99±0.27 ng.m -3 (Ebinghaus et al, 2002, Temme et al, 2003, Terra Nova Bay (0.9±0.3 ng.m -3 (Sprovieri et al, 2002)), McMurdo (1.20±1.08 ng.m -3 (Brooks et al, 2008b) and the continental South Pole station 0.54 ± 0.19 ng.m -3 (Brooks et al, 2008a).…”
Section: Resultssupporting
confidence: 75%
“…Oxidized Hg compounds, such as the operationally defined reactive gaseous Hg (RGM) and Hg associated with airborne particulate matter (HgP) are normally found at much lower concentrations (in the pg.m -3 range) in the troposphere. The atmospheric lifetime of Hg(0) dramatically decreases to a few hours during fast oxidation processes involving bromine radicals as observed in various locations including lower latitudes (Obrist et al, 2011), the Arctic (Steffen et al, 2008) and the Antarctic (Brooks et al, 2008b, Ebinghaus et al, 2002, Sprovieri et al, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…The station is located at 70°39 0 S, 80°15 0 W, on the Ekströmisen, 8 km from Atka Bay [Ebinghaus et al, 2002a].…”
Section: Methodsmentioning
confidence: 99%
“…[7,8] Recent studies in both the Arctic and Antarctic have revealed that elemental gaseous mercury is depleted from the atmosphere at certain times of the year and deposited in the snow-pack, which brings it into the biosphere. [9][10][11][12][13][14] Mercury depletion events seem to correlate with tropospheric ozone reduction, [9-11, 13, 14] which is known to be a result of the catalytic destruction of ozone molecules by chlorine and bromine atoms, thus yielding molecular oxygen and ClO or BrO. [15][16][17] In this connection, the reaction Hg + BrO!HgO + Br has been proposed as an important path for mercury depletion in the troposphere.…”
Section: Introductionmentioning
confidence: 99%